IMPLEMENTASI METODE TARJAMAH HARFIAH DALAM MENINGKATKAN MAHARAH QIRA’AH BAGI MAHASISWA STAI KH. MUHAMMAD ALI SHODIQ - Moh Ikhsani; Choiruddin (LPPM STAI Muhammadiyah Probolinggo, 2023)
The purpose of this study is to determine the effect of implementing the literal translation method on Maharah Qira’ah in Arabic language learning at STAI KH. Muhammad Ali Shodiq. Arabic is a very important subject to teach in madrasahs. In relation to the significance of the Arabic language, the Ministry of Religious Affairs of the Republic of Indonesia's grand plan states that the subjects of Islamic Education and Arabic Language in the content standards indicate that Arabic serves as the primary tool for understanding Islamic teachings. This research is a quantitative study of the pre-experimental type. The results of this study show that the application of the literal translation method has a positive and significant impact on Maharah Qira’ah among second-semester students of the Arabic Language Education program at STAI KH. Muhammad Ali Shodiq. By using this learning method, students' abilities in Arabic, particularly in Maharah Qira’ah, have improved.